Analisis Pengaruh Nilai Tukar Inflasi Dan Tingkat Suku Bunga Terhadap Indeks Harga Saham Studi Kasus Pada Jakarta Islamic Index Periode 2010-2014 - Rahmawati, Susana Dwi; , Dra. Wafiatun Mukharomah, M.M (2016)
This study aimed to analyze about the effect of the exchange rate, inflation, and interest rates on JII stock price index during the period 2010-2014. The sampling technique used purposive sampling technique. Methods of analysis used in this study is the classical assumption test, multiplier linear regression test, t test, F test, 〖 R〗^2 test with a level of signifacnt at 5% or 0,05. Simultaneous test results show that all the variables simultaneously significant effect on the stock price index JII. While the partial test results show that the exchange rate and interest rate significantly affect the stock price index JII. Otherwise variable inflation does not significantly affect the stock price index JII. R^2 test result 57,10 % variance of stock price index JII can be explained by the variable exchange rate, inflation, and interest rates while the remaining 42,90 % is explained by other factors outside the model studied. Keywords : The exchange rates, Inflation, Interest rates, Stock price index JII